Implementación de un servicio de reportes regionales sobre la gestión del canon para la Asociación de Contribuyentes del Perú - Labarthe Saric, Raul Antonio (2021)
This project was started in 2019 to design a new service by the non-governmental organization “Asociación de Contribuyentes del Perú” (ACP) aimed at creating royalty management reports for mining and oil companies. Since 2017, the ACP has faced a political situation marked by corruption of officials and companies in the country. The ACP required the development of new services to continue operating, since the situation fostered mistrust in public-private relations, making it difficult for citizen organizations to continue formulating recommendations for bills. Faced with the need of not depending on politics, the ACP created a service for mining and oil companies for the elaboration and communication of reports on the management of the canon and royalties for the purpose. This idea arose from analyzing the problem of mismanagement of these resources in mining and oil regions that, in addition to environmental externalities, suffered from municipal inefficiency, poverty, and gaps in public services by their citizens. This report was designed based on a management diagnosis of the transfers of income from the exploitation of natural resources using various industrial engineering tools. The regional management reports consisted on socioeconomic evaluation, measurement of the administrative fragmentation of resources, analysis of management quality, estimation of new resources, and recommendations for regulatory reforms. This initiative allowed obtaining income of 128 thousand soles in 2019 for the NGO, which generated an increase of 6 % compared to 2018. The operating margin of the service reached 43,8 % and an increase in appearances in media of 44 % compared to 2018.